Digitalization in the EFL Classroom: Teachers’ and Students’ Perspectives - Muhammad Yauri, Andi; Tenri Ajeng, Andi; Darwis, Nirwana; Adisaturrahimi, Andi; Musfirah; Wahyu; Dian Hidayat, LD (Universitas Islam Negeri Raden Intan Lampung, 2026)
Digitalization has become an integral component of English as a Foreign Language (EFL) instruction, particularly in secondary education contexts where technology increasingly mediates teaching and learning practices. This study investigates how digitalization is perceived and enacted in junior high school EFL classrooms from the perspectives of teachers and students. Employing a qualitative descriptive design, data were collected through structured interviews and systematic non-participant classroom observations involving two English teachers and two eighth-grade students from two public junior high schools in Watampone, South Sulawesi, Indonesia. Thematic analysis guided by the Miles, Huberman, and Saldña interactive model revealed four interrelated themes: (1) accessibility and diversification of learning resources, (2) student engagement, motivation, and learner autonomy, (3) instructional delivery and assessment efficiency, and (4) pedagogical, technical, and behavioral challenges. The findings demonstrate that digitalization meaningfully enhances instructional quality and learner engagement; however, its pedagogical value is contingent upon teacher mediation, intentional instructional design, and institutional support. Rather than functioning as an inherently transformative solution, digitalization emerges as a pedagogically mediated process whose efficacy is shaped by contextual, infrastructural, and competency-related factors. This study contributes context-sensitive qualitative insights into digital EFL practices at the secondary level in a regional Indonesian setting, highlighting the indispensable role of aligning technological integration with explicit pedagogical goals.